Meaning through language contrast. - Jaszczolt, Katarzyna; Turner, Ken, 1956- (Pragmatics & beyond, 2003)
These volumes contain selected papers from the Second International Conference on Contrastive Semantics and Pragmatics that was held at Newnham College, University of Cambridge, in September 2000. They include papers on negation, temporality, modality, evidentiality, eventualities, grammar and conceptualization, grammaticalization, metaphor, cross-cultural pragmatics and speech acts and the semantics-pragmatics boundary. There are contributions by, amongst many others, Les Bruce, Ilinca Crainiceanu, Thorstein Fretheim, Saeko Fukushima, Ronald Geluykens, Javier Gutiérrez-Rexach, Klaus von Heusi.